2021
DOI: 10.1111/jre.12852
|View full text |Cite
|
Sign up to set email alerts
|

NCOA4‐mediated ferritinophagy promoted inflammatory responses in periodontitis

Abstract: Background/Objectives Iron homeostasis plays a crucial role in the combat against pathogen invasion. Ferrous iron can trigger generous production of reactive oxygen species (ROS) by Fenton reaction. Nuclear receptor coactivator 4 (NCOA4), a selective cargo receptor to deliver ferritin to lysosome, may trigger release of ferritin‐bound iron into the cytosol. The aim of the present study was to explore whether NCOA4‐mediated ferritinophagy participated in the pathogenesis of periodontitis, and its role in promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…Both animal experiments and clinical experiments have shown that the iron content in periodontitis sites was higher than that in healthy periodontal sites [ 68 ]. It has been reported that free iron concentrations are significantly up-regulated 6–12 h after periodontal infection [ 86 ], and these high concentrations of iron have been shown to be more favorable for the maturation of certain periodontal-dominant pathogenic bacteria biofilms [ 87 ]. To satisfy their growth and reproduction, micro-organisms need to compete with their hosts for iron.…”
Section: Ferroptosis and Periodontitismentioning
confidence: 99%
“…Both animal experiments and clinical experiments have shown that the iron content in periodontitis sites was higher than that in healthy periodontal sites [ 68 ]. It has been reported that free iron concentrations are significantly up-regulated 6–12 h after periodontal infection [ 86 ], and these high concentrations of iron have been shown to be more favorable for the maturation of certain periodontal-dominant pathogenic bacteria biofilms [ 87 ]. To satisfy their growth and reproduction, micro-organisms need to compete with their hosts for iron.…”
Section: Ferroptosis and Periodontitismentioning
confidence: 99%
“…Based on the RNA-seq, Davanian H confirmed that the elevated levels of locally produced cytokines in the periodontium [ 24 ]. A recent study including molecular biology experiments showed that NCOA4, one of the FRGs, is related to the occurrence and development of periodontitis, indicating that iron homeostasis plays an important role in the pathogenesis of periodontitis [ 20 ]. Ferroptosis triggers excess intracellular ROS and promotes lipid peroxidation, which is critical for inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the analysis results of the downregulated genes include NCOA4, which is important in periodontitis. An article pointed out that periodontitis is mostly correlated with NCOA4 -mediated ferritinophagy in intracellular iron level regulation [ 20 ], p38/hypoxia inducible factor-1α pathway activation, and bromodomain-containing protein 4 and cyclin-dependent kinase 9 transcription modulation mediated butyrate-triggered NCOA4 expression in periodontal ligament fibroblasts [ 19 ]. Conversely, NCOA4 over-expression increased sensitivity to ferroptosis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations